Awareness and perception of risk for cervical cancer among women in Ogbomoso, Nigeria (2017)
Background: Cervical cancer, though preventable, remains the leading cause of cancer death among women in developing countries after breast. Lack of awareness and access to preventive methods remains a key factor contributing to high levels of cervical cancer in these populations. Objectives: The study aimed to assess the level of awareness of, and perception of risk for, cervical cancer among women attending Bowen University Teaching Hospital (BUTH) general outpatient clinic. Methodology: This was a cross-sectional study conducted at the BUTH, Ogbomoso. Data were obtained from 318 consenting women using systematic random sampling method. An interviewer-administered questionnaire was used to gather information about their sociodemographic characteristics, marital and reproductive history, and awareness and perception of risk for cervical cancer. Data were analyzed using Statistical Package for the Social Sciences version 23.0. The level of statistical significance was set at P < 0.05. Results: Awareness for cervical cancer and its screening tests were 22.6% and 17.9%, respectively, with major sources of information being from health talks and hospital staffs. About 5.7% believed that they may be at risk whereas only 1.6% had ever 2 = 10.46,2 = 20.05, P = 0.005) and early coitarche (been screened. Perception of risk is significantly associated with age ( P = 0.015). Overall, respondents’ attitude was positive to cervical cancer screening. Conclusion: The level of awareness of cervical cancer and screening was low among the respondents. Increased media campaign about its risks and preventive measures is urgently needed.